Poznavanje dovoljenih in nedovoljenih drog med petošolci v občini Logatec - Šemrov, Marija (Obzornik zdravstvene nege, 2005)
The article presents the results of the research on familiarity with drugs in young people which was carried on the fifth-graders in the municipality of Logatec. The research results revealed that 11% of them have had experience with alcoholic drinks, 10% smoked cigarettes, and one has already experimentedwith illegal drugs. The fact that children know more about drugs names than about their real effects has been proved. Their attitude towards legal drugs is more permissive that towards illegal drugs. The data can serve as the basis of health education programs.
Keywords: ankete; Child; droge; mamila; Mamilla; Nedovoljene snovi; osnovnošolci; Otrok; Questionnaires; Schools; Street Drugs; Substance Abuse; Šole